Edukasi Gaya Hidup dan Pola Makan Remaja dalam Pencegahan Penyakit Gagal Ginjal dengan Metode Active Learning pada Siswa SMA Muhammadiyah Al Kautsar PK Kartasura : Pengabdian - Syafriati, Ani; Indri, Indri; Bestari, Salwa Alifa; Ramadhani, Zukhrofa Rizkiana; Rahayu, Sri; Widodo, Arif (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Kidney failure is a growing public health problem, including among adolescents, largely influenced by unhealthy lifestyles and poor dietary habits. Early prevention through health education is essential to reduce the risk of kidney disease in the future. This community service program aimed to improve adolescents’ knowledge and awareness regarding healthy lifestyles and balanced dietary patterns for the prevention of kidney failure. The program was implemented at SMA Muhammadiyah Al Kautsar PK Kartasura and targeted senior high school students using an Active Learning approach, including group discussions, simulations, role play, interactive quizzes, and case studies. The activities began with early health screening, such as blood pressure measurement, body mass index assessment, and random blood glucose testing, followed by interactive health education sessions. Evaluation was conducted using pre-test and post-test assessments to measure changes in students’ knowledge levels. The results demonstrated a significant improvement in knowledge, with the proportion of students categorized as having good knowledge increasing from 18.82% in the pre-test to 91.76% in the post-test. In addition, students showed high enthusiasm and active participation throughout the program.